Sebaran kasus malaria berdasarkan variabel cuaca dengan pendekatan spasial-temporal di Kabupaten Kulon Progo, Yogyakarta Tahun 2005-2015 - Nilasari Nilasari; Lutfan Lazuardi (Berita Kedokteran Masyarakat (BKM), 2017)
Spatial-temporal distribution of malaria cases based on wind speed and humidity in Kulon Progo Regency of DIYPurposeThe purpose of this study was to determine the correlation of weather variables (humidity and wind flow velocity) in 2005-2015.MethodsThis secondary data study used 1439 cases of malaria and weather data for 11 years. The research design was an ecological study, with analysis using time/series graph and bivariate analysis.ResultsStatistical analysis showed that the variables significantly related to the distribution of malaria cases were wind flow velocity lag 0, wind flow velocity speed lag 1, wind flow velocity lag 2, wind flow velocity lag 3. The humidity was not statistically related to the distribution of malaria cases.ConclusionThere was a relationship between wind speed up to three months earlier, while the humidity was not related to the spread of malaria cases. Kulon Progo District Health Office needs cross-sectoral cooperation with other agencies, and malaria control programs need to pay attention to weather patterns in order to decrease morbidity and mortality due to malaria.